Implant-based multiparameter telemonitoring of patients with heart failure (IN-TIME): a randomised controlled trial - Hindricks, Gerhard; Taborsky, Milos; Glikson, Michael; Heinrich, Ullus; Schumacher, Burghard; Katz, Amos; Brachmann, Johannes; Lewalter, Thorsten; Goette, Andreas; Block, Michael; Kautzner, Josef; Sack, Stefan; et al. (Lancet (London, England), 2014)
BACKGROUND: An increasing number of patients with heart failure receive implantable cardioverter-defibrillators (ICDs) or cardiac resynchronisation defibrillators (CRT-Ds) with telemonitoring function. Early detection of worsening heart failure, or upstream factors predisposing to worsening heart failure, by implant-based telemonitoring might enable pre-emptive intervention and improve outcomes, but the evidence is weak. We investigated this possibility in IN-TIME, a clinical trial. METHODS: We did this randomised, controlled trial at 36 tertiary clinical centres and hospitals in Australia, Europe, and Israel. We enrolled patients with chronic heart failure, NYHA class II-III symptoms, ejection fraction of no more than 35%, optimal drug treatment, no permanent atrial fibrillation, and a recent dual-chamber ICD or CRT-D implantation. After a 1 month run-in phase, patients were randomly assigned (1:1) to either automatic, daily, implant-based, multiparameter telemonitoring in addition to standard care or standard care without telemonitoring. Investigators were not masked to treatment allocation. Patients were masked to allocation unless they were contacted because of telemonitoring findings. Follow-up was 1 year. The primary outcome measure was a composite clinical score combining all-cause death, overnight hospital admission for heart failure, change in NYHA class, and change in patient global self-assessment, for the intention-to-treat population. The trial is registered with ClinicalTrials.gov, number NCT00538356. FINDINGS: We enrolled 716 patients, of whom 664 were randomly assigned (333 to telemonitoring, 331 to control). Mean age was 65·5 years and mean ejection fraction was 26%. 285 (43%) of patients had NYHA functional class II and 378 (57%) had NYHA class III. Most patients received CRT-Ds (390; 58·7%). At 1 year, 63 (18·9%) of 333 patients in the telemonitoring group versus 90 (27·2%) of 331 in the control group (p=0·013) had worsened composite score (odds ratio 0·63, 95% CI 0·43-0·90). Ten versus 27 patients died during follow-up. INTERPRETATION: Automatic, daily, implant-based, multiparameter telemonitoring can significantly improve clinical outcomes for patients with heart failure. Such telemonitoring is feasible and should be used in clinical practice. FUNDING: Biotronik SE & Co. KG.
Keywords: senioři; Telemedicine; Defibrillators, Implantable; telemedicína; Europe; výsledek terapie; Evropa; mužské pohlaví; Monitoring, Ambulatory; Izrael; ženské pohlaví; Austrálie; Humans; defibrilátory implantabilní; Israel; srdeční selhání; Australia; Female; Aged; ambulantní monitorování; Treatment Outcome; Heart Failure; lidé; Male